Sistema de monitoramento e automação de estufa com ESP32 para cultivo de hortaliças - Assis, Lukas Farias Martins de (Universidade Federal de São Carlos, 2026)
The cultivation of leafy vegetables and greens in small-scale greenhouses depends on the proper maintenance of environmental variables such as temperature, air humidity, soil moisture, and luminosity. When this control is performed manually, irrigation failures, insufficient ventilation, inadequate lighting, and difficulties in maintaining uniform environmental conditions may occur, compromising plant development and the overall efficiency of the cultivation system. Given the growing appreciation for fresh food produced under more controlled conditions, the development of automation solutions capable of reducing such limitations becomes increasingly relevant. In this context, this work presents the development of a small-scale automated greenhouse based on the ESP32 microcontroller, intended for the cultivation of leafy vegetables and greens. The system continuously monitors the main environmental variables and automatically actuates irrigation, ventilation, and lighting systems based on previously defined limits. To achieve this, sensors and actuators are integrated into an embedded system capable of performing data acquisition, control, and supervision routines. In addition to local automation, the operating data are made available on the ThingSpeak platform, enabling remote monitoring of greenhouse behavior over time. Thus, the work proposes a low-cost solution for protected cultivation, with the potential to improve management regularity, reduce operational failures, and contribute to vegetable production in a monitored and automated environment.
ESP32-based greenhouse monitoring and automation system for vegetable cultivation
Keywords: Sistemas embarcados; Embedded systems; ESP32; Estufa automatizada; Automated greenhouse; Cultivo protegido; Protected cultivation; Automação agrícola; Agricultural automation; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS; 12. Consumo e Produção Responsáveis